Liquidity indicators for the Norwegian government bond market - Vetle Øye Opheim (Norges Bank, 2019)
An objective of Norges Bank Government Debt Management is to meet the government's borrowing requirement at the lowest possible cost. At the same time, Government Debt Management shall seek to maintain a yield curve out to 10 years. Market liquidity is of importance for both objectives. This article investigates liquidity developments in the Norwegian government bond market since 2010 with the aid of four indicators that comprise a composite liquidity index. I also examine whether Norwegian banks' funding costs have affected government bond market liquidity in the period 2010-2018, but find no clear correlation.
hdl:11250/2653103
Keywords: 330; Government bonds; liquidity; indicators